Prevalence of Alzheimer's disease and related dementias among veterans experiencing housing insecurity. Issue 7 (10th November 2021) - Jutkowitz, Eric; Halladay, Christopher; Tsai, Jack; Hooshyar, Dina; Quach, Lien; O'Toole, Thomas; Rudolph, James L.
Abstract: Introduction: Housing insecure veterans are aging, but the prevalence of Alzheimer's disease and related dementias (AD/ADRD) in the population is unknown. Methods: We calculated the prevalence of AD/ADRD diagnoses in 2018 among veterans that experienced homelessness, were at‐risk for homelessness, or were stably housed. We determined acute care (emergency department, hospitalizations, psychiatric hospitalizations), and any long‐term care (nursing home, and community‐based) use by housing status among veterans with an AD/ADRD diagnosis. Results: The overall prevalence of AD/ADRD diagnoses for homeless, at‐risk, and stably housed veterans was 3.66%, 13.48%, and 3.04%, respectively. Housing insecure veterans with AD/ADRD used more acute care, and were more likely to have a nursing home admission compared to stably housed veterans. At risk, but not homeless veterans, were more likely to use US Department of Veterans Affairs–paid home and community‐based care than stably housed veterans. Discussion: The prevalence of AD/ADRD diagnoses is greater among housing insecure veterans than stably housed veterans.